Mn-salen catalysed benzylic C-H activation for the synthesis of aryl [(18)F]CF3-containing PET probes. - Carroll,L; Evans,H; Spivey,AC; Aboagye,EO (Chemical Communications, 2015)
The development of a Mn-salen complex catalysed oxidative benzylic fluorination of non-activated C-H bonds using [(18)F]fluoride is described for installation of [(18)F]CHRF, [(18)F]CR2F and particularly [(18)F]CF3 containing groups in the presence of other functional groups.